The Relationship between Diet and Stress with Gastritis Symptoms in Adolescents at Integrated Agricultural Vocational Schools - Tilla, Marda; Arneliwati, Arneliwati; Zulfitri, Reni (CV. Rayyan Dwi Bharata, 2024)
Adolescence is a productive age that can experience lifestyle changes that don't pay attention to health, making them susceptible to gastritis symptoms. Common causes of gastritis include improper eating patterns, such as inappropriate frequency or timing of meals, eating excessively and quickly, or consuming foods that are stimulating (too spiced and spicy). Gastritis can easily attack individuals who have irregular eating patterns. Stress affects changes in physiological functions in the body's systems, one of which is the digestive system. Stress can cause decreased appetite, stomach emptying, increased stomach acid, resulting in pain in the stomach. This study aims to determine the relationship between diet and stress and symptoms of gastritis in adolescents. This research is a cross sectional study conducted on 271 teenagers at the Integrated Agricultural Vocational School, Riau Province. The data collection tool is a questionnaire that is valid and has high reliability. The results of the analysis carried out using the chi square test showed that there was a significant relationship between diet and stress and symptoms of gastritis in adolescents as evidenced by a correlation value of 0.000 α 0.05. After conducting research, the results showed that poor eating patterns and high levels of stress can result in symptoms of gastritis.